THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND CORPORATE SOCIAL PERFORMANCE: EVIDENCE FROM INDONESIAN LISTED COMPANIES - Irawan, Evelyn
The concepts of Corporate Governance (CG) and Corporate Social Performance (CSP) have become attractive topics in Indonesia due to its close relationship with the company value. CG and CSP give a lot of benefits for the companies such as strengthening the companies image and maintaining the companies sustainability. Financial crisis that happened during 1997-1998 in Indonesia also made companies start to put their attention toward CG. At that time, companies with bad corporate governance tend to have a higher chance of bankruptcy because the companies didn’t have good communication system and unbalanced proportion of company ownership that can lead to the corruption. Companies became more aware of this concepts because Indonesia government also supports CG and CSP by issuing some law. To support companies in term of good corporate governance, national committee on governance released Indonesia’s code of good corporate governance on 2006. While to support corporate social performance, Indonesia government issues Law No. 40 of 2007 on Limited Company and Government Regulation No. 47 of 2012 on Corporate Social Responsibility and Environment on Limited Company. As the society becomes more fascinated by the social issues such as inequality and global warming, investors and companies are also become more attracted to these social issues. Investors want to contribute in restoring the conditions while hopefully generate some financial return. By knowing the relationship between two variables, it will help social investors to pick the best companies by putting CG variables into considerations. Social investors can analyze which CG variables that enhance CSP and focusing on those variables. Therefore, companies should put more attention on those variable in order to attract the investors. It motivates the author to investigate whether CG has an impact on CSP or not. The purpose of this study is to analyze the relationship between CG and CSP of 245 Indonesian companies in 2013. Multiple regression analysis is conducted in this study to analyze the relationship between independent variables namely ownership of government shareholders, ownership of foreign shareholders, ownership of managerial shareholders, independent outside managerial, audit committee, board size, and dependent variable, which is CSP. In this study, CSR (Corporate Social Responsibility) is measured by using 7 models of CSP namely total CSP, economic, environmental, social, total disclosure, total strength and total concern. CG data are gathered from company annual reports in 2013, while CSP data are gathered from Firmialy and Nainggolan (2016). These findings indicate that ownership of government shareholders has positive and significant effect toward the CSP in model 1 (total CSP), model 2 (economic), model 4 (social), model 5 (total disclosure), and model 7 (total concern). While, ownership of managerial shareholders have positive and significant effect toward the CSP in model 3 (environmental) and model 6 (total strength). While, other variables have no significant effect toward the CSP. It means that companies that are dominated by government and managerial shareholders tend to have higher CSP. Social investors can consider ownership of government shareholders and managerial shareholders before making investment decisions. This study is also expected to provide information for corporate so they will have more consideration on CG and CSP, analyze which CG variables that will enhance CSP; and avenue for future study.